The protective capability of the laser welded armour steel plates. (May 2020) - Pacek, D; Kolodziejczak, P; Grzelak, K; Torzewski, J; Podgorzak, P
Despite the intensive development of plastics and composite materials in the case of armours employed to protect vehicles, armour steel remains a material commonly and effectively used. This is especially evident in the base armour of armoured vehicles, where the body is made of welded armour steel plates. However, the area of joining both the weld and the heat affected zone are sensitive areas with the reduced protective capability. In the case of laser welding in comparison with methods such as shielded metal arc welding and gas metal arc welding, it is possible to narrow down the above mentioned areas. The paper presents the results of research on the protective capability of welded zone of armour steel plates with a hardness of 500 HB. In the first part of the work, in order to select the proper parameters for the bonding process, different connection variants were made and their microstructure and selected mechanical properties were analysed. After selecting the best variant of the welding process, samples (200 mm × 200 mm) consisting of two welded plates with dimensions 100 mm × 200 mm were made for testing. The thickness of the plates was selected in such a way that in the areas outside the bonding zone, the lack of complete perforation by the projectiles used in the tests is guaranteed. The samples were shot at the weld location and at different distances from the weld to verify, for the chosen method of joining steel plates, if the welded armour loses its protective capability and, possibly, how wide this area may be.